1998
DOI: 10.1021/la971161s
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Sodium Dodecyl Sulfate at the Surface of Aqueous Solutions of Poly(vinylpyrrolidone) Studied by Neutron Reflection

Abstract: The surface excess of sodium dodecyl sulfate (SDS) in aqueous solutions of SDS and the polymer poly(vinylpyrrolidone) (PVP) has been measured as a function of SDS and PVP concentrations using neutron reflection. Below the critical aggregation concentration (CAC) the adsorption of SDS is increased by the presence of PVP, indicating that the two components interact cooperatively at the surface. Between the CAC and the critical micelle concentration (CMC) of the surfactant there is a slight depletion of SDS from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
154
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(176 citation statements)
references
References 34 publications
(47 reference statements)
21
154
0
1
Order By: Relevance
“…In a series of papers, Thomas, Penfold, and co-workers (12)(13)(14), using specular neutron reflection techniques on PEO/ SDS and PVP/SDS systems, demonstrated in general terms that below T 1 , mixed surface films of polymer and surfactant are present, but above T 1 the polymer is displaced. Increases in surfactant concentration in the surface occur beyond T 1 and can occur to some extent beyond T 2 : the actual concentration of polymer affects the particular behavior observed.…”
Section: Other Surface Analyses Films Foamsmentioning
confidence: 99%
“…In a series of papers, Thomas, Penfold, and co-workers (12)(13)(14), using specular neutron reflection techniques on PEO/ SDS and PVP/SDS systems, demonstrated in general terms that below T 1 , mixed surface films of polymer and surfactant are present, but above T 1 the polymer is displaced. Increases in surfactant concentration in the surface occur beyond T 1 and can occur to some extent beyond T 2 : the actual concentration of polymer affects the particular behavior observed.…”
Section: Other Surface Analyses Films Foamsmentioning
confidence: 99%
“…Although complexes of this substance formed with conventional surfactants in aqueous solutions is the subject of numerous studies (20,21), the PVP adsorption films at the liquid-gas interface have been poorly investigated, probably because of experimental difficulties. For example, PVP is effectively invisible in the neutron reflection experiment (21).…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption at an interface depends upon the competition between complex formation in the bulk and at interface. There are numerous studies on the associative nature of polymers in bulk solutions [65][66][67][68][69][70][71][72][73][74][75][76]. Philip et al [77] have reported that the interaction between a neutral polymer (PVA), an ionic surfactant (SDS) and colloid can lead to three different states which depends upon the sequence of adsorption of polymer and surfactant on the colloidal interface.…”
Section: Polymer-amphiphile Interactionsmentioning
confidence: 99%